SELF-ACTUALIZATION IN SHEKAR KAPUR’S THE GOLDEN AGE: A HUMANISTIC PSYCHOLOGICAL APPROACH - KRISTIANI, INA (2010)
The problem of this study is how the major character, Queen Elizabeth actualizes herself in Shekar Kapur’s The Golden Age. The objective of this study is to analyze Shekar Kapur’s The Golden Age based on the structural element and Maslow’s humanistic psychological approach.